A five-day course of ivermectin for the treatment of COVID-19 may reduce the duration of illness. (February 2021) - Ahmed, Sabeena; Karim, Mohammad Mahbubul; Ross, Allen G.; Hossain, Mohammad Sharif; Clemens, John D.; Sumiya, Mariya Kibtiya; Phru, Ching Swe; Rahman, Mustafizur; Zaman, Khalequ; Somani, Jyoti; Yasmin, Rubina; Hasnat, Mohammad Abul; et al.
Highlights: Ivermectin, an FDA-approved anti-parasitic agent, was found to be an inhibitor of SARS-CoV-2 replication in the laboratory. Ivermectin may be effective for the treatment of early-onset mild COVID-19 in adult patients. Early viral clearance of SARS-CoV-2 was observed in ivermectin treated patients. Remission of fever, cough and sore throat did not differ among treatment groups. No severe adverse event was observed. Larger trials will be needed to confirm these preliminary findings. Abstract: Ivermectin, a US Food and Drug Administration-approved anti-parasitic agent, was found to inhibit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replication in vitro. A randomized, double-blind, placebo-controlled trial was conducted to determine the rapidity of viral clearance and safety of ivermectin among adult SARS-CoV-2 patients. The trial included 72 hospitalized patients in Dhaka, Bangladesh, who were assigned to one of three groups: oral ivermectin alone (12 mg once daily for 5 days), oral ivermectin in combination with doxycycline (12 mg ivermectin single dose and 200 mg doxycycline on day 1, followed by 100 mg every 12 h for the next 4 days), and a placebo control group. Clinical symptoms of fever, cough, and sore throat were comparable among the three groups. Virological clearance was earlier in the 5-day ivermectin treatment arm when compared to the placebo group (9.7 days vs 12.7 days; p = 0.02), but this was not the case for the ivermectin + doxycycline arm (11.5 days; p = 0.27). There were no severe adverse drug events recorded in the study. A 5-day course of ivermectin was found to be safe and effective in treating adult patients with mild COVID-19. Larger trials will be needed to confirm these preliminary findings.